Implementasi Kegiatan Keagamaan Dalam Pembentukan Akhlak Siswa Di MTs Miftahul Ulum Cermenan Ngoro Jombang - Mifta Alviana; Desy Naelasari (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
This study aims to 1.Describe the religious activities at MTs Miftahul Ulum Cermenan Ngoro Jombang 2. To describe the morals of students at MTs Miftahul Ulum Cermenan Ngoro Jombang. 3. Describe the implementation of religious activities in the moral formation of students at MTs Miftahul Ulum Cermenan Ngoro Jombang. 4. Describe the factors supporting and inhibiting the formation of students' morals at MTs Miftahul Ulum Cermenan Ngoro Jombang. The method used is a qualitative method with a qualitative descriptive design using data collection techniques, namely observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis. The results showed that: 1. Religious activities at MTs Miftahul Ulum Cermenan Ngoro Jombang include: Reading QS. Yasin and QS. Waqi'ah, dhuha prayer in congregation, tahlil, istighotsah, commemoration of the Birthday of the Prophet SAW 2. Morals of students at MTs Miftahul Ulum Cermenan Ngoro Jombang are polite, friendly, and yet a small number of students still violate good morals to teachers, parents and fellow students 3. The application of religious activities is very influential in the formation of students' morals. Through religious activities can make students have good morals. The implementation of religious activities also requires methods to be used in the formation of students' morals including: a. Habituation method, b. Exemplary Method, c. Advice Method, d. Punishment Method. 4. a. Supporting factors: the commitment of the principal and teachers in carrying out activities by working together, enthusiastic students in carrying out activities, motivation of parents, infrastructure. b. Inhibiting factors: students who do not care, families who are less supportive, less supportive community environment, parents who do not cooperate with the madrasah.